2020
DOI: 10.1093/pubmed/fdaa101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicidal ideation, plan, attempts and its associated factors in selected rural and urban areas of Puducherry, India

Abstract: Background The Union Territory of Puducherry has a high rate of suicide in India. This study aims to find the prevalence of suicidal ideation, plan and suicide attempts and the risk factors of suicidal behaviours. Methods This community-based cross-sectional study was conducted among adults aged 18 years and above in rural and urban areas of Puducherry, India. Columbia Suicide Severity Rating Scale questionnaire was used. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…These findings go along with that of Rajappa et al [35] in which they suggested that suicidal behaviors are attempts to escape negative emotions that occur when people lack emotion control tools when they are distressed. Also, these findings shared similarities with Singh et al [36] results where they found that 74.6% of suicidality ideated to end pain and 12.1% to get attention. As well, these findings were in agreement with the findings of Stubbing and Gibson's [37] study where 9 focus group discussions were conducted with youth in New Zealand.…”
Section: Discussionsupporting
confidence: 88%
“…These findings go along with that of Rajappa et al [35] in which they suggested that suicidal behaviors are attempts to escape negative emotions that occur when people lack emotion control tools when they are distressed. Also, these findings shared similarities with Singh et al [36] results where they found that 74.6% of suicidality ideated to end pain and 12.1% to get attention. As well, these findings were in agreement with the findings of Stubbing and Gibson's [37] study where 9 focus group discussions were conducted with youth in New Zealand.…”
Section: Discussionsupporting
confidence: 88%
“…13 In contrast to our findings, studies in India by Singh A, Lingeswaran A, and Purushothaman P found more number of females attempting suicide, which could be due to differences in the population sampled. 17,19,20 In accordance with the results of a qualitative study on attempted suicide among young people in India, the majority of our subjects who attempted suicide were unmarried. 21 Low educational attainment, low socioeconomic status, and involvement in the agricultural sector were found to be the vulnerable demographics for heightened suicide risk in our sample.…”
Section: Discussionsupporting
confidence: 86%
“…13 In a study done among rural and urban populations of Puducherry in South India, most participants enumerated reasons for attempting suicide as being family-related, alcohol-related, finance-related, loss of loved one, loneliness, unemployment, health-related, and work/jobrelated among various other reasons and family-related issues being more prevalent of all. 14 Another study reported the presence of psychiatric illness, substance use disorders, and severe medical illness (such as cancer, head injury, peptic ulcer disease, HIV/AIDS, and chronic pain) as some of the other factors that result in suicidal ideation. 15 Research suggests that suicide attempts tend to recur with each attempt showing increased capability of lethality and almost half of serious suicide attempters make another attempt within 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] In Indian rural setting, most of the girls get married between 18 and 25 years, so it is not surprising that other studies also suggested suicides and attempted suicides are more common in young and newly married women because of physical and mental illness, disturbed emotional relationship, economic hardship, sexual and financial victimization. [ 6 7 18 ]…”
Section: Discussionmentioning
confidence: 99%